Kinotopic consumptionscapes: Impacts of autonomous mobility on consumption and sociotechnical futures - Braun, Róbert (Marketing & Menedzsment, 2017)
THE AIMS OF THE PAPER A ’post-car’ world is very much determined by new forms of technologically enabled mobilities. The paper claims that autonomous ’mobility-things’ are versions of Foucauldian heterotopias: kinotopias (moving spaces) that will have a deep impact on our future societies by rearranging consumptíonscapes as well as the politics of interconnectedness. Kinotopic mobility creates spatial as well as temporal fluidity. METHODOLOGY Utilizing action-network-theory the paper analyses, through looking at different future world scenarios, how kinotopic mobility will rearrange our consumptíonscapes. MOST IMPORTANT RESULTS The paper looks at the imagined worlds’ potential impacts on sociotechnical futures and draws conclusions for present day innovation, research practices and policies in autonomous mobility.